2014
DOI: 10.1017/s0033291714001299
|View full text |Cite
|
Sign up to set email alerts
|

Does asking about suicide and related behaviours induce suicidal ideation? What is the evidence?

Abstract: There is a commonly held perception in psychology that enquiring about suicidality, either in research or clinical settings, can increase suicidal tendencies. While the potential vulnerability of participants involved in psychological research must be addressed, apprehensions about conducting studies of suicidality create a Catch-22 situation for researchers. Ethics committees require evidence that proposed studies will not cause distress or suicidal ideation, yet a lack of published research can mean allaying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
183
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 257 publications
(194 citation statements)
references
References 19 publications
4
183
0
7
Order By: Relevance
“…Findings indicated that those respondents who did report thoughts of self-harm or suicide did not report higher distress as a result of participation in the study, nor did it impact upon their return to complete a second survey several years later. These findings complement existing literature which indicates that inclusion of such questions does not increase suicidal ideation or distress and may in fact have positive outcomes for participants experiencing these symptoms [8,20]. The findings of this paper confirmed the high levels of trauma in the study sample.…”
Section: Discussionsupporting
confidence: 86%
“…Findings indicated that those respondents who did report thoughts of self-harm or suicide did not report higher distress as a result of participation in the study, nor did it impact upon their return to complete a second survey several years later. These findings complement existing literature which indicates that inclusion of such questions does not increase suicidal ideation or distress and may in fact have positive outcomes for participants experiencing these symptoms [8,20]. The findings of this paper confirmed the high levels of trauma in the study sample.…”
Section: Discussionsupporting
confidence: 86%
“…(12) Acknowledging and discussing suicide may reduce, instead of aggravate, suicidal ideation. Asking about suicide may help primary care physicians to identify high-risk patients who require urgent intervention (such as hospitalisation) and to uncover risk factors, some of which are amenable to intervention.…”
Section: What Can I Do In My Practice?mentioning
confidence: 99%
“…In the general population, it is established that discussing suicide does not induce thoughts of suicide but rather, may offer beneficial long term outcomes (Dazzi et al 2014). It is unknown if perseverative thinking in some individuals with ASD without adaptive coping skills may incline them to dwell on the topic without benefit.…”
Section: Future Considerations: Practice-informed Research and Evidenmentioning
confidence: 99%